Studies on Physico-chemical Parameters to Assess the Water Quality of Chandidongri Distt. Rajnandgaon for Drinking and Agriculture Purpose - Biswas, S.N.; Mohabey, Hemlata; Naik, M.L. (Asian Journal of Chemistry, 2016)
Quality of water for its potential use depends on different physico-chemical parameters. In order to assess water quality of Chandidongri village of Chhattisgarh State, twenty water samples were collected from different sources viz., open well, pond, hand pump, for three seasons, i.e., rainy, winter and summer; moreover, simultaneously three samples of water were collected from nearby city area as control. Temperature, odour, colour, taste, turbidity, conductivity, TDS, total hardness and sodium absorption ratio (SAR) value were determined for the purpose. It was found that all the samples collected have physico-chemical parameters in the range recommended by ISI and WHO. The sodium absorption ratio value of water samples of village area of Chandidongri were lower in comparison to sodium absorption ratio value of water samples collected from city area and is excellent for irrigation.